Der heimliche Hund - Michels, Tilde 1920-2012 (Dt. Taschenbuch-Verl., 1994)
Lea wants a dog, but her parents say no. Lea finds an animal shelter, and is allowed to walk Axi, a Schnauzer. Finally she persuades her parents to let her keep Axi.
Keywords: Children and animals -- Fiction; Dogs -- Fiction; German language materials; Mädchen; Hund; Tierheim; Kinderbuch